Lecturers Pedagogical Concepts in Reducing Student Anxiety in Statistics Courses - Judijanto, Loso; Putro, Adi Nugroho Susanto (Journal for Lesson and Learning Studies, 2024)
Graduate students show high levels of anxiety in studying Statistics; This anxiety affects their appreciation of statistics courses. This is urgent to research because there are differences between theory, expectations, and reality in the field. So, it is necessary to research to find out the appropriate pedagogical behavior of Statistics teachers to reduce postgraduate student anxiety. The research method used is a descriptive case study approach woven into a sequential explanatory design. The research subjects were lecturers and postgraduate students. Primary data was obtained from 99 postgraduate students regarding their level of anxiety in the field of Statistics and their experiences with lecturers' pedagogical behavior. Additionally, 12 graduate students were interviewed about their pedagogical behaviors that reduced their anxiety in Statistics. To triangulate primary data, evidence of assessment of lecturers' teaching practices was obtained from the university's Directorate of Academic Planning and Quality Assurance Unit. The results and findings show that there are 17 strategic lecturer pedagogical behaviors in general behavior (affective factors and pedagogical practices) and specific pedagogy (cognitive factors) which reduce postgraduate students' statistics anxiety and increase positive attitudes towards statistics studies. This is the heuristic contribution that this research offers to the application of processing efficiency theory. Therefore, the introduction of these pedagogical behaviors and their openness during the teaching of Statistics will help reduce the anxiety level of graduate students in the field of Statistics.